Research on Energy Conversion and Damage Features of Unloading Instability of Sandstone under High Stress - Zhiyuan Hou; Chuanbo Hao; Fukun Xiao; Gang Liu (Advances in Civil Engineering)
In order to explore the failure characteristics of sandstone under unloading conditions in deep zone with high stress, constant axial pressure and unloading confining pressure tests were conducted on a yellow sandstone sample under different initial confining pressures using the French ROCK600-50 triaxial tester, and the mechanical properties, energy conversion characteristics, and damage evolution law of sandstone failure under unloading conditions were obtained. The test results showed that the axial deformation, the confining pressure for failure, and the shear fracture energy during the failure process of sandstone under the unloading state were positively correlated with the initial confining pressure; the dilatancy amount and speed and the radial deformation were negatively correlated with the initial confining pressure, exhibiting the characteristics of dilatancy under low confining pressure and compression under high confining pressure. Before the unloading point, almost all the energy absorbed by the rock under low initial confining pressure was converted into elastic energy, while part of the energy absorbed under high initial confining pressure was converted into dissipated energy, and the higher the confining pressure, the greater the proportion of the dissipated energy converted. The higher the initial confining pressure, the greater the elastic energy, radial deformation energy, and dissipated energy at the rock fracture point. The larger the unloading confining pressure, the greater the postpeak failure energy and surplus energy of sandstone, and the greater the increase in the proportion of elastic energy converted into surplus energy. The higher the confining pressure, the larger the damage value at the unloading point; the damage speed in the unloading stage was significantly greater than that in the loading stage.